Environmental Problems and Their Solution in Light of the Life and Teachings of Holy Prophet Muhammad (S.A.W) - Abdul Rehman; Umme Aymen Abdul Razzaq (jihat-ul-islam, 2022)
When our Lord created the universe, it was at the summit of its beauty and grace. The earth was an even more beautiful part of it. Its oceans and rivers, springs and waterfalls, land and mountains, burning deserts and oases, gardens and fertile green fields, soft and tender breeze, singing birds, crawling insects, and running animals make the universe more and more fascinating. Every corner of the universe our Lord created only to serve the stay of man on the earth, and man has been reaping benefits from these blessings for thousands of years, maintaining a balanced relationship with nature until recently. Then comes a time when humankind began to treat Mother Nature heedlessly by constructing artificial ways of living and consequently caused her to lose balance. It was a shift of human instinct from the natural to the unnatural. In the name of development, the man gave way to the industrial revolution without prudent check and balance to manipulate the natural resources, no matter how harmful it proved for nature. The insane craze of man to industrialize the world revolutionized life and made it easier, but, at the same time, it ignored the importance of natural resources for the stability of the ecosystem. As a result, the balance of nature it had in the past vanished, and humankind exposed itself to the natural disasters previously unknown. It was because the humans valued not the blessings the earth brought in as a balanced nature. It happened even though with the settlement of man on the earth, our Lord also descended His message accordingly. His message came down with the help of the messengers and the prophets. The prophets delivered the message of God to humanity and taught them His ways by practicing them. The whole life of the prophet Mohamed (PBUH) has been an example of the ways of God for humanity. He taught the world not only the rights of God but also the rights of all other living things on human beings. And definitely, the earth's ecosystem is one of them. He set several pivotal rules that stabilize the ecosystem and thus protect the environment of nature. So, in the face of current environmental issues, we must study the life of the prophet Mohamed (PBUH) very deeply and with great concentration to help teach the world that the earth and its eco stability are as important as human life.